No evidence of human disturbance to vegetation in the Zoige Region (north-eastern Tibetan Plateau) in the last millennium until recent decades - Zhang, Yanrong; Li, Yunqing; Liu, Lina; Wang, Nannan; Cao, Xianyong (Palaeogeography, palaeoclimatology, palaeoecology, 2022)
A high-resolution record (~5–20 years per sample) of pollen, charcoal, total organic carbon (TOC), and total nitrogen (TN) was analysed from a core obtained from a small lake (Xing Co) on the northeastern Tibetan Plateau. Findings shed light on vegetation change and its driving forces over the last ~1440 years and the impact of recent human activities. Between ca. 580 and 1300 CE, vegetation was alpine meadow, dominated by Cyperaceae with low percentages of Poaceae and Artemisia. Pollen spectra indicate that vegetation shifted to dry alpine steppe dominated by Poaceae and Artemisia between 1300 and 1470 CE, possibly as a response to reduced precipitation and cooler temperatures linked to the transition from the Medieval Warm Period (MWP) to the Little Ice Age (LIA). A further significant increase of Poaceae from 1770 to 1910 CE indicates consolidation of the alpine steppe. However, after 1910 CE, pollen spectra are characterized by decreasing Poaceae abundance and increasing abundances of Artemisia, Cyperaceae, Ranunculaceae, Thalictrum, and Polygonaceae, with high pollen richness and evenness. These recent vegetation changes are probably caused, at least in part, by enhanced human impacts. Furthermore, our analysis also shows an significant increase in percentages of Pediastrum and Potamogeton together with a sharp increase in TN after ca. 1990 CE, suggesting eutrophication of the lake water. Therefore, our record suggests that human activities did not have any significant impact on the composition of the vegetation until recent decades at Xing Co. •A high resolution pollen spectra covering last 1440 years completed for the northeastern Tibetan Plateau.•Vegetation changes were triggered mainly by climate changes until 1910 CE.•Human activities could disturb both of terrestrial and aquatic ecosystems since 1910 CE.